2019
DOI: 10.1002/eco.2148
|View full text |Cite
|
Sign up to set email alerts
|

Controlling factors affecting the presence and distribution of Didymosphenia geminata in lakes and rivers of the Neuquén province, Argentina

Abstract: The diatom Didymosphenia geminata (D. geminata) is an invasive periphytic species from the Northern Hemisphere. D. geminata occurrence and mat formation in Patagonia Argentina dates from 2010, spreading throughout Patagonia (provinces of Chubut, Neuquén, Río Negro, and Santa Cruz) by 2017. In 2012, the Surveillance and Monitoring Program was implemented by Neuquén government entities. Within this programme, nine sampling campaigns have been conducted at 91 sites including streams, rivers, lakes, reservoirs, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Analysis of data from a surveillance and monitoring program operated in Patagonia Argentina since 2012 found a broader range of environmental conditions associated with Didymosphenia than previously reported, especially for P, N, magnesium, and temperature, and raised concerns about the susceptibility of water bodies (Beamud et al, 2019). In contrast with previous literature that suggested that low P levels act as the primary trigger of mucilage production in Didymosphenia , analysis of river samples from Tennessee, United States, found mat formation correlated with water chemistry, temperature, and discharge, but not dissolved P, though the relationships varied with season (Hix & Murdock, 2019).…”
Section: Algaementioning
confidence: 99%
“…Analysis of data from a surveillance and monitoring program operated in Patagonia Argentina since 2012 found a broader range of environmental conditions associated with Didymosphenia than previously reported, especially for P, N, magnesium, and temperature, and raised concerns about the susceptibility of water bodies (Beamud et al, 2019). In contrast with previous literature that suggested that low P levels act as the primary trigger of mucilage production in Didymosphenia , analysis of river samples from Tennessee, United States, found mat formation correlated with water chemistry, temperature, and discharge, but not dissolved P, though the relationships varied with season (Hix & Murdock, 2019).…”
Section: Algaementioning
confidence: 99%